Dyeing of Silk Fabric with Eco-Friendly Natural Dyes Obtained from Spathodea campanulata and Cordia sebestena: A Comparison - Kumaresan, M.; Palanisamy, P.N.; Kumar, P.E. (Asian Journal of Chemistry, 2013)
Bleached silk fabric was dyed with natural dyes obtained from the flower of Spathodea campanulata and Cordia sebestena. The colour fastness properties and colour strength of dyed silk fabric were determined and compared. From the comparative study of fastness properties and colour strength of the dyed cotton samples, Spathodea campanulata in simultaneous mordanting method with 3 % mordant combination gives better results as compared to the natural dye obtained from the flower of Cordia sebestena.